2023
DOI: 10.1108/ijppm-01-2022-0018
|View full text |Cite
|
Sign up to set email alerts
|

Orientation and absorptive capacity towards sustainability: a missing link between sustainability and performance

Abstract: PurposeThis study investigates economic sustainability through orientation and absorptive capacity.Design/methodology/approachThe researchers developed a conceptual framework based on vigorous literature for this investigation. This study targeted managers from Pakistan's SME sector as respondents and employed cross-sectional data. In total, the authors based this study's findings on 192 valid cases.FindingsThe structural equation modeling (SEM) results highlight that innovation orientation (IO), customer orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 120 publications
(421 reference statements)
0
1
0
Order By: Relevance
“…Although previous studies have reported a positive association between digital competence and innovation performance, particularly with reference to the importance of strategic alignment in using sustainability goals to achieve competition [111][112][113][114], there are few studies which examine the specific issue of how DT can affect sustainability innovation from the perspective of information processing. Equally, there is little research that inductively examines the role of digital adaptability.…”
Section: Structural Model Analysismentioning
confidence: 99%
“…Although previous studies have reported a positive association between digital competence and innovation performance, particularly with reference to the importance of strategic alignment in using sustainability goals to achieve competition [111][112][113][114], there are few studies which examine the specific issue of how DT can affect sustainability innovation from the perspective of information processing. Equally, there is little research that inductively examines the role of digital adaptability.…”
Section: Structural Model Analysismentioning
confidence: 99%